The Influence Of Digital Marketing And The Use Of Digital Wallets On Consumer Behavior On Ecommerce Platforms - Saepul Nazar; M Ramaddan Julianti; Refi Nabilah Royadi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the influence of digital marketing and digital wallet usage on consumer behavior within e-commerce platforms. The research is motivated by the rapid digitalization of transactions and the growing importance of digital marketing strategies and payment technologies in shaping consumer decision-making. A quantitative approach was employed, using multiple linear regression analysis based on data collected from 120 respondents who actively use e-commerce and make purchases via digital wallets. The findings reveal that both digital marketing and digital wallets have a positive and significant effect on consumer behavior, both individually and simultaneously, contributing 45.3% to the variation in consumer behavior. These results offer strategic implications for businesses and MSMEs in leveraging digital marketing and seamless transaction technologies to enhance customer loyalty and optimize service efficiency in the digital economy.